METODE KAISA DALAM PERSPEKTIF MULTIPLE INTELEGENCE - Salamah, Umi (Hunafa: Jurnal Studia Islamika, 2019)
Memorizing the Qur'an usually uses conventional methods (drill, listen, imitate) and is less attractive when applied to children. The purpose of this study was to analyze memorizing the Qur'an using the Kaisa method in the perspective of multiple intelligence. The Kaisa method is a way of memorizing the Koran which is oriented to memorization and understanding of the verses of the Koran along with their meanings through movements or kinesthetic which are adapted to the meaning of each verse so as to make it easy to understand and remember every verse of the Qur'an given . This research method is descriptive qualitative, data collection is through observation, interviews, and documentation. The research results obtained that memorizing the Qur'an using the Kaisa method is able to accommodate multiple intelligences (multiple intelligence)